1999
DOI: 10.1007/s11745-999-0470-9
|View full text |Cite
|
Sign up to set email alerts
|

Column and high‐performance size exclusion chromatography applications to the in vivo digestibility study of a thermoxidized and polymerized olive oil

Abstract: This study aimed (i) to design an in vivo model to study fat digestibility, and (ii) to apply this design to test the in vivo digestibility of a highly thermoxidized olive oil. True digestibility of unheated olive oil was tested 2, 4, 6, and 7 h after administering 1 g of olive oil/100 g body weight to young adult Wistar rats by means of esophageal probes. Remaining gastrointestinal lumen fat showed an inversely linear relationship (r= -0.9932; P < 0.001) with the length of the experiment. A 4-h test was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 32 publications
2
34
1
Order By: Relevance
“…Our group has found that the concentration of oligomers increases with the use of oils. 1,17,26 Moreover, by comparing the present results of oligomers with those found in an olive oil heated under the same conditions, 16 it can be deduced that sunflower oil becomes very much more polymerized than olive oil does. After a 4 h administration, the amount of luminal fat remaining appears higher in the animals in which the heated sunflower oil was tested.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Our group has found that the concentration of oligomers increases with the use of oils. 1,17,26 Moreover, by comparing the present results of oligomers with those found in an olive oil heated under the same conditions, 16 it can be deduced that sunflower oil becomes very much more polymerized than olive oil does. After a 4 h administration, the amount of luminal fat remaining appears higher in the animals in which the heated sunflower oil was tested.…”
Section: Discussionsupporting
confidence: 55%
“…Aspects related to phospholipid, bile acids and cholesterol influences on the measurements have been discussed and published previously. 16 Because the addition of cholesterol to the samples increases the area related to free fatty acids, the cholesterol content in the luminal fat samples was measured using Boehringer Mannheim's (Mannheim, Germany) enzymatic colorimetric method, and the HPSEC free fatty acids data were corrected. 16 …”
Section: Fat Digestibility Testmentioning
confidence: 99%
See 2 more Smart Citations
“…If so, the small difference in fecal oils excreted from the control and the gluten groups cannot be explained. Sanchez-Muniz et al 21) fed young adult Wistar rats a diet containing olive oil heated at 180 for 150 h to get the true digestibility coefficient. They reported that thermoxidized compounds from abused olive oil were poorly but actively hydrolyzed and absorbed in vivo.…”
Section: Discussionmentioning
confidence: 99%